Kerentanan kesehatan penyintas bencana terhadap perubahan iklim - Fikri, Mohammad; Firmansyah, Firmansyah; Krisnasari, Sendhy; Ashari, Muhammad Rizki; Megasari, Anitatia Ratna; Afdhal, Muhammad Ridha (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Global climate change has increased the frequency and intensity of natural disasters, including in previously affected areas such as Palu City. Disaster-affected communities relocated to the Tondo Permanent Housing (Huntap) continue to face potential disaster risks. Purpose: To examine the health vulnerability of disaster survivors to the impacts of climate change in Huntap Tondo. Method: . A qualitative approach with a case study design was employed, and data were collected through in-depth interviews using the snowball sampling technique. Data analysis was conducted using content analysis supported by NVIVO 12 software. Data validity was ensured through source triangulation and peer debriefing. Results: Communities still face the potential for disasters such as mudflows, strong winds, and the risk of landslides, which impact access to clean water and environmental conditions. Infrastructure, such as drainage, is deemed inadequate, while building structures raise doubts about their durability. However, mitigating behaviors such as community service and social adjustment are emerging within the community. Conclusion: Although residents have been relocated to permanent housing, they remain vulnerable to the impacts of climate change and require strengthened mitigation systems and supporting infrastructure Keywords: Climate Change; Survivor; Susceptibility. Pendahuluan: Perubahan iklim global telah meningkatkan frekuensi dan intensitas bencana alam, termasuk di wilayah yang telah terdampak sebelumnya seperti Kota Palu. Masyarakat penyintas bencana yang direlokasi ke Hunian Tetap (Huntap) Tondo masih menghadapi potensi risiko bencana. Tujuan: Untuk mengkaji kerentanan kesehatan masyarakat penyintas terhadap dampak perubahan iklim di Huntap Tondo. Metode: Penelitian kualitatif dengan desain studi kasus dan pengumpulan data dilakukan melalui wawancara mendalam dengan teknik snowball sampling. Analisis data dilakukan menggunakan pendekatan analisis isi (content analysis) menggunakan aplikasi NVIVO 12. Validitas data diuji melalui triangulasi sumber dan peer debriefing Hasil: Masyarakat masih menghadapi potensi bencana seperti banjir lumpur, angin kencang, dan risiko tanah longsor yang memengaruhi akses terhadap air bersih dan kondisi lingkungan. Infrastruktur seperti drainase dinilai belum memadai, sementara struktur bangunan menimbulkan keraguan terhadap ketahanannya. Meski demikian, terdapat perilaku mitigatif seperti kerja bakti dan penyesuaian sosial yang tumbuh di kalangan masyarakat Simpulan: Meskipun telah direlokasi ke hunian tetap, masyarakat masih mengalami kerentanan terhadap dampak perubahan iklim dan perlu penguatan sistem mitigasi serta infrastruktur pendukung. Kata Kunci : Kerentanan; Penyintas; Perubahan Iklim.